Effects of Branched Fins on Alumina and N-Octadecane Melting Performance Inside Energy Storage System - Weera, Wajaree; Maneengam, Apichit; Saeed, Abdulkafi Mohammed; Aissa, Abderrahmane; Guedri, Kamel; Younis, Obai; Marzouki, Riadh; Asogwa, Kanayo K. (Frontiers in Physics, 2022)
Phase change material (PCM) energy storage systems provide a number of benefits, includ-ing the ability to store energy at a nearly constant temperature and a higher energy density. As a consequence, this study intends to develop a numerical simulation for optimizing the melting performance of a PCM in a variety of tubes, including those with branching fins. Four examples are assessed in relation to a suspension of Al2O3/n-octadecane paraffin that contains heated fins. A numerical technique based on the finite element method is used to solve the dimensionless governing system (FEM). The average liquid percentage over the flow zone in question is computed. The primary results indicated that altering the number of heated fins might have an effect on the flow structures, irreversibility of the system, and melting process. Case four, with eight heated fins, likewise produces the greatest average liquid fraction values and completes the melting process in 850s. Additionally, when 6% nano-enhanced PCM is used instead of pure PCM, the melting process is accelerated by 28.57 percent.